Wewenang Negara dalam Pengaturan Penyelenggaraan Sistem Elektronik Dikaitkan dengan Kebebasan Berekspresi di Dunia Digital - Ari Maulana Yudha Pratama; Isharyanto Isharyanto; Achmad Achmad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the state's authority in organizing electronic systems related to freedom of expression in the digital world. The development of technology that gives rise to a dilemma between the needs or activities of society and regulations to protect public interests and individual human rights, especially freedom of expression, makes it necessary to have regulations that accommodate both of these things. Through a prescriptive normative legal research method with a statutory approach, through an analysis of laws and regulations, legal literature, and international human rights instruments, this study examines the state's authority in regulating the implementation of electronic systems that are pro-freedom of expression. The results of the study indicate that the state has the authority to regulate the implementation of electronic systems to determine and enforce restrictions on a person's human rights, which in this case is shown through the ability to terminate access to content. However, the implementation of the provisions that have been in effect has the potential to violate the right to freedom of expression because of the possibility of restrictions on rights that do not meet the principles of legality, legitimate purposes, and proportionality as regulated by laws and regulations, especially the constitution and international human rights standards.